UJI AKTIVITAS ANTIOKSIDAN EKSTRAK AIR DAN EKSTRAK METANOL BEBERAPA VARIAN BUAH KENITU (Chrysophyllum cainito L.) DARI DAERAH JEMBER - Moch. Amrun H.; Umiyah Umiyah; Evi Umayah U (The East Java Biological Society, 2007)
Star apple or Chrysophyllum cainito L., family Sapotaceae; which is indigenous in Central America has been grown locally arround Jember, East Java. Ethnobotanical data exhibits its medicinal properties such as: soothing inflammation in laringitis and pneumonia, treatment for diabetes mellitus and cancer remedy which are related to free radical mechanism. Therefore, it is necessary to determine its free radical scavenger activity.There are three types of Jember’s star apple fruit (local name: kenitu): big size, green color with round shape (kenitu hijau bulat); medium size, green color with oval shape (kenitu hijau lonjong); and small size, red purplish color with round shape (kenitu merah bulat). Previous research shown that both water and methanol extracts of kenitu hijau lonjong has DPPH free radical scavenger activity as its antioxidant capacity. In recent research the DPPH free radical scavenger activity was performed on both water and methanol extract of these three types of kenitu. The results showed that kenitu merah bulat exhibits the highest antioxidant activity of these three types with IC50 = 426.118 and 169.094 ppm for methanol and water extracts sequentially in 60th minutes.